Anthropometric hand dimensions in a population of Iranian male workers in 2012. Issue 1 (2nd January 2016) - Mirmohammadi, Seyyed Jalil; Mehrparvar, Amir Houshang; Mostaghaci, Mehrdad; Davari, Mohammad Hossein; Bahaloo, Maryam; Mashtizadeh, Samaneh
Abstract : Background . The mismatch between the hand size of workers and the size of industrial instruments is a growing concern; it can lead to various musculoskeletal complications. Currently, there are few reliable studies available to address this concern in Iran. This study was conducted to measure 30 upper-extremity parameters in a group of Iranian industrial workers. Methods . This study is a cross-sectional study on 529 workers. The study population was randomly selected from male Iranian industrial workers who were referred to the Yazd hospital occupational medicine clinic for surveillance evaluations. Results . The M ( SD ) age of the participants was 30.13 (8.29) years. Statistical analysis was performed using the mean, standard deviation and 5th, 50th and 90th percentiles for each measured hand dimension. A considerable number of dimensions were significantly different between the measurements of right and left hands in each examinee. The results showed significant differences between Iranian hand size and that of other populations. Conclusion . This study provided a valuable databank of hand dimensions in a population of Iranian male workers. These data can be used by manufacturers in designing high-quality hand-tools and industrial gloves, taking into consideration Iranian worker characteristics.